Characterization of the Physical, Chemical, and Sensory Properties of Mocaf and Menir Analog Rice with the Addition of Skim Milk and Konjac Glucomannan - Astuti, Santi Dwi; Ayuningtyas, Laksmi Putri; Dewi, Ervina Mela; Novitasari, Dian (Indonesian Journal of Food Technology, 2025)
Background: Food diversification based on local resources is essential to reduce dependence on rice while improving the nutritional and functional quality of alternative staple foods. Purpose: This study aimed to compare the physicochemical and sensory characteristics of four analog rice formulations: those based on modified cassava flour (mocaf) (BA1), rice grits flour (BA2), and both materials supplemented with skim milk and konjac glucomannan (KGM) (BA3 and BA4). Method: The experiment was conducted using a non-factorial Completely Randomized Design (CRD) with four treatments differing in base material and functional ingredient addition. Analog rice was produced through an extrusion process, followed by analyses of proximate composition, starch content, total sugars, dietary fiber, starch and protein digestibility, mineral content (sodium and potassium), color parameters (L*, a*, b*), water activity (Aw), and sensory evaluation by 40 untrained panelists. Result: The results showed that BA1 exhibited higher moisture content, dietary fiber, and potassium levels, along with lower Aw and sodium content, compared to BA2. In contrast, BA2 demonstrated higher protein content, energy value, and lightness (L*) than BA1. The incorporation of skim milk and KGM in BA3 and BA4 significantly affected most measured parameters, increasing moisture, ash, protein, total sugar, and soluble fiber contents, while reducing starch content, insoluble fiber, starch and protein digestibility, and energy value. Sensory evaluation indicated that BA1 outperformed BA2 in terms of texture and stickiness, whereas the addition of skim milk and KGM—particularly in BA3—significantly enhanced overall acceptability, flavor, and aroma. These findings suggest that the combination of mocaf, skim milk, and konjac glucomannan produces analog rice with improved functional and organoleptic properties, highlighting its potential as a locally sourced alternative staple food.